Association of perioperative ibuprofen exposure with post-tonsillectomy bleeding requiring operative management. (March 2021) - Miller, Ashley L.; McCarty, Justin C.; Bergmark, Regan W.; Gadkaree, Shekhar K.; Cohen, Michael S.; Diercks, Gillian R.; Keamy, Donald J.; Mankarious, Leila A.; Hartnick, Christopher J.
Abstract: Introduction: Pediatric tonsillectomy is one of the most common surgical procedures performed in the United States. The safety of ibuprofen use after surgery is debated given concern for increased bleeding. The primary objective of this study was to compare the rate of post-tonsillectomy hemorrhage requiring operative management in patients who received ibuprofen perioperatively vs. patients who did not. Methods: Retrospective cohort study of patients 0–18 years old who underwent tonsillectomy with or without adenoidectomy (T&A) with recorded inpatient medication administration data at a single tertiary care institution from 1/2005-1/2019. The association between perioperative medication administration and return to operating room (OR) for control was evaluated using multivariable logistic regression adjusted for patient demographics and operative indication. Secondary outcomes evaluated included the time to operative bleed when it occurred. Results: A total of 4098 patients with a median age of 6 years old (IQR 4–10) underwent T&A over the study period. The overall rate of post-tonsillectomy hemorrhage requiring OR was 3.37% (n = 138/4098). After adjustment for confounders, the odds of bleeding requiring OR did not differ significantly between the ibuprofen (OR 1.16, 95% CI (0.76, 1.74), 3.55%, n = 41/1, 156, p = 0.47) and non-ibuprofen groups (3.30%, n = 97/2942). The median time to bleeding requiring OR was postoperative day 6.5 (IQR6-8) in the ibuprofen group and day 6 (IQR 3–8) in the non-ibuprofen group. Conclusions: No difference in post-tonsillectomy hemorrhage requiring OR was observed between patients receiving perioperative ibuprofen versus those patients not receiving this medication. Additional research is required to definitively determine a safe dose and interval for ibuprofen administration following tonsillectomy.